ANALISIS PEMAHAMAN SISWA SMA N1 PERCUT SEI TUAN TERHADAP KONSEP DASAR BARISAN DAN DERET - Kairudin; Brilyant Alvindo Sihombing; Aldryanto Lumban Gaol; Martin A Hutauruk; Jhose R Siburian; Firman Satria Tafonao (Universitas Nias Raya, 2025)
This study aims to conduct an in-depth analysis of the level and profile of students’ understanding at SMA Negeri 1 Percut Sei Tuan regarding the fundamental concepts of Sequences and Series in mathematics learning. Conceptual understanding is a fundamental aspect of comprehensive mathematical mastery, as it not only involves the ability to apply formulas but also requires logical reasoning and comprehension of the relationships between concepts. Initial indications reveal a significant gap between students’ ability to use formulas mechanically and their deeper conceptual understanding. This research employs a Mixed Methods approach with an Exploratory Sequential design, beginning with the collection of quantitative data through written tests administered to 30 eleventh-grade science students (Class XI MIA), followed by semi-structured interviews with selected students to further explore their conceptual grasp. Quantitative analysis shows that approximately 70% of students were able to answer procedural questions—those solvable through direct formula application. However, only about 30% of students succeeded in solving more complex problems requiring deeper reasoning and conceptual understanding. The qualitative findings reinforce these results, indicating that students tend to memorize formulas without understanding their underlying meaning or origin, and often struggle to distinguish between the concepts of sequences and series. Therefore, a shift in instructional approach is needed, emphasizing exploration, conceptual discussion, and holistic understanding.